Sustainable Development Communication in Digitalization of Waste Management through Digital Waste Banks in Serang City - Agus Kristian; Ahmad; Erlin Pramesti Agustina (Ilomata International Journal of Social Science, 2026)
Waste management in Serang City faces challenges, such as low community participation and limited facilities, leading to increased waste volume and environmental pollution. The Digital Waste Bank, as an innovative solution, leverages digitalization to enhance waste management effectiveness through community participation. This study, applying a Sustainable Development Communication approach, aims to analyze communication strategies in digital waste management, identify factors influencing community participation, and propose an effective collaborative communication model between government, communities, and the private sector in the context of the Digital Waste Bank (BSD) in Serang City. Using a qualitative case study approach, data were gathered through in-depth interviews, participatory observations, and focus group discussions. The findings highlight that adaptive communication strategies, the use of social media, and community-based approaches are crucial for engaging the public. Key obstacles include low digital literacy and limited technology access, but opportunities exist in the form of economic incentives and CSR support. The study concludes that structured, cross-sector collaboration significantly enhances the sustainability of digital waste management. Recommendations include improving digital literacy and establishing an integrated communication system between stakeholders to ensure program sustainability.